2007
DOI: 10.1248/bpb.30.1987
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Effects of Mouth Washing on Removal of Drug Residues Following Inhalation of Fluticasone Propionate Dry Powder

Abstract: Inhaled corticosteroids are widely used for treatment of asthma, though local adverse effects, such as candidiasis and hoarseness, are often seen in patients treated with those drugs. Therefore, the Packaging Inserts enclosed with such medications recommend mouth washing after inhalation for prevention of local adverse effects. In spite of that recommendation, candidiasis has been reported by patients who washed their mouth after inhalation.1) Therefore, we carried out a series of studies to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A further study suggested that ‘throat washing’ reduced colonisation of the oropharynx with Candida species in patients inhaling fluticasone propionate using a dry powder inhaler. 36 Yokoyama et al 37 showed that different types of mouth rinsing may be important, with rinsing and gargling more effective than rinsing alone for removing oropharyngeal fluticasone propionate deposited after using a DPI. An additional potential benefit of mouth rinsing after inhaling corticosteroids might be reduced deposition in the gut and thus reduced systemic exposure.…”
Section: Beliefs Supporting Data and Panel Conclusionmentioning
confidence: 99%
“…A further study suggested that ‘throat washing’ reduced colonisation of the oropharynx with Candida species in patients inhaling fluticasone propionate using a dry powder inhaler. 36 Yokoyama et al 37 showed that different types of mouth rinsing may be important, with rinsing and gargling more effective than rinsing alone for removing oropharyngeal fluticasone propionate deposited after using a DPI. An additional potential benefit of mouth rinsing after inhaling corticosteroids might be reduced deposition in the gut and thus reduced systemic exposure.…”
Section: Beliefs Supporting Data and Panel Conclusionmentioning
confidence: 99%
“…Previous literature proposed the pharynx and larynx regions as difficult to remove areas and that it is necessary to spend more effort (5-8 times compared to easy to remove areas) in order to remove up to 90% deposited particles. 15 Lee et al suggested to use the immediate diet method instead of mouth washing after the use of ICS. Participants were educated to have a meal within five min immediately after ICS inhalation.…”
Section: Local Adverse Eventsmentioning
confidence: 99%